New frameworks for community-based cultural tourism - Conti, Alfredo Luis (2014)
Cultural heritage becomes an asset which allows widening the tourism offer or developing tourism in places where the activity had not been traditional. Local communities play a significant role in the development of tourism, especially in those cases where tourism is perceived as an instrument for local development. The implementation of community-based tourism requires planning and capacity building among all stakeholders. In this framework, the purpose of this paper is analysing a community-based tourism programme, Tourism Villages, implemented in the province of Buenos Aires, Argentina.